Individual and Psychological Aspects of Inquisitiveness Manifestation in Students - I B Kudinova; N V Bogomazova (RUDN Journal of Psychology and Pedagogics, 2011)
The article deals with the problem of inquisitiveness of the personality. The specific individual and psychological features of its manifestations in students are considered.